Gene manipulation in mycobacteria - Konícek, J; Konícková-Radochová, M; Slosárek, M (Folia microbiologica, 1991)
Gene manipulation in mycobacteria developed in two phases. In the first phase genes of mycobacteria were transferred into cells of E. coli and Streptomyces lividans. In the second phase, heterologous genes were transferred into mycobacteria either with a shuttle plasmid or hybrid plasmids. A prerequisite for successful gene manipulation in mycobacteria was a thorough understanding of plasmids in mycobacteria. Construction of recombinant DNA molecules contributed not only to the fact that mycobacteria did not remain outside the mainstream of modern genetic research but also to their present practical importance.
Keywords: bakteriální geny; transfekce; Transfection; Mycobacterium; Genes, Bacterial; Plasmids; plazmidy; Escherichia coli; Streptomyces